The effect of β-cell dysfunction on reproductive outcomes of PCOS undergoing IVF or ICSI embryo transfer cycles: a retrospective cohort study - Huang, Wenle; Liu, Chang; Ding, Lin; Li, Yan; Zhou, Haisu; Wang, Shuwei; Yang, Haiyan (Frontiers in Endocrinology, 2024)
Objective: To investigate the effects of β-cell dysfunction on IVF outcomes in women with PCOS.Methods: This retrospective cohort study includes 1,212 women with PCOS undergoing their first IVF cycle between September 2010 and December 2019.Beta-cell dysfunction was measured by homeostasis model assessment of β-cell function (HOMA-β) index.In quartiles of HOMA-β, the incidence of miscarriage dramatically increased from 10.2% (Q1) to 31.1% (Q4) (P for trend <0.001). Likewise, the incidence of miscarriage in quartiles of HOMA-β also showed a similar trend (P for trend <0.001).After adjusting for confounding factors, logistic regression analyses showed that high HOMA-IR values were independently associated with a high risk of miscarriage, with the odds ratios (OR) and 95% confidence intervals for quartiles 2-4 versus quartile 1 were 1.30 (0.69-2.46), 1.82 (0.97-3.43), and 3.57 (1.86-6.85), respectively (P for trend <0.001). When analyzed jointly, women in the highest HOMA-IR and highest HOMA-β group exhibited the highest risk for miscarriage compared with all other groups. Furthermore, higher HOMA-IR values were associated with higher risks of miscarriage among PCOS women regardless of HOMA-β values.Conclusions: β-cell dysfunction is independently associated with increased miscarriage rate and decreased live birth rate in women with PCOS. It also plays a synergistic role with IR in terms of the reproductive outcomes, while the influence of IR overweighs that of β-cell dysfunction.